PATHOMORPHOLOGICAL CHANGES CAUSED BY EXPOSURE TO EXTREME TEMPERATURES: A FORENSIC AND HISTOLOGICAL ANALYSIS - Zakirova Alfiya Idrisovna (Web of Journals Publishing, 2026)
Background: Exposure to extreme temperatures remains a significant cause of injury and death worldwide. Objective: To analyze morphological and histological changes associated with thermal burns and frostbite in forensic practice. Methods: Histological examination of skin and internal organs obtained from fatal cases of exposure to high and low temperatures was performed. Results: High-temperature exposure resulted in coagulative necrosis, vascular congestion, and systemic organ damage. Low-temperature exposure caused vascular spasm, ice crystal formation, ischemia, and characteristic gastric hemorrhages (Wischnewsky spots). Conclusion: Distinct histopathological patterns allow reliable differentiation between hyperthermia- and hypothermia-related deaths.
Keywords: Thermal injury, frostbite, hyperthermia, hypothermia, forensic pathology.